2008
DOI: 10.7326/0003-4819-149-7-200810070-00008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: d-Dimer to Predict Recurrent Disease after Stopping Anticoagulant Therapy for Unprovoked Venous Thromboembolism

Abstract: In patients who have completed at least 3 months of anticoagulation for a first episode of unprovoked VTE and after approximately 2 years of follow-up, a negative D-dimer result was associated with a 3.5% annual risk for recurrent disease, whereas a positive D-dimer result was associated with an 8.9% annual risk for recurrence. These rates should inform decisions about the balance of risks and benefits of prolonging anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(151 citation statements)
references
References 44 publications
9
133
1
8
Order By: Relevance
“…D-Dimer is a well-studied biomarker in the diagnosis and management of VTE and a risk factor for VTE recurrence with potential implications for deciding on the duration of oral anticoagulation for secondary VTE prophylxis in noncancer patients. [26][27][28][29] sPselectin is a cell adhesion molecule that promotes thrombus formation and exhibits procoagulant properties per se. 26,30,31 Recent data suggest that sP-selectin is associated with primary and recurrent thrombosis in noncancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…D-Dimer is a well-studied biomarker in the diagnosis and management of VTE and a risk factor for VTE recurrence with potential implications for deciding on the duration of oral anticoagulation for secondary VTE prophylxis in noncancer patients. [26][27][28][29] sPselectin is a cell adhesion molecule that promotes thrombus formation and exhibits procoagulant properties per se. 26,30,31 Recent data suggest that sP-selectin is associated with primary and recurrent thrombosis in noncancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews that examined the use of D-dimer measured after discontinuation of anticoagulants for unprovoked VTE reported approximately a doubling of the risk of recurrence for those with a positive D-dimer result compared with those with a negative D-dimer. 71,72 In only one of the studies included in these meta-analyses was D-dimer measurement used to manage patients. The PROLONG study was a multicentre trial of 708 patients with a first unprovoked venous thromboembolic event who had received at least 3 months of oral anticoagulant therapy.…”
Section: D-dimer Testing For Duration Of Anticoagulant Therapymentioning
confidence: 99%
“…[22][23][24][25][26][27][28] A meta-analysis, including seven studies of 1,888 patients who completed at least 3 months of anticoagulation, found that a D-dimer level of less than approximately 500 ng/mL ("a negative test") was associated with a 3.5% (95% CI, 2.7-4.3) annual risk of recurrence, whereas a D-dimer over this level ("a positive test") was (Table 2). 29 Potential difficulties of this approach, however, are lack of agreement and different cutpoints for the various D-dimer assays (there is no D-dimer "standard"). Clinicians must, therefore, rely on an assay manufacturer's cutpoint for a positive or negative D-dimer test based on individual studies using D-dimer to assess recurrence risk.…”
Section: Clinical Vignette: a 52-year-old Male Presented With An Unprmentioning
confidence: 99%